A study of dysphagia symptoms and esophageal body function in children undergoing anti‐reflux surgery. Issue 6 (1st July 2018) - Omari, T; Connor, F; McCall, L; Ferris, L; Ellison, S; Hanson, B; Abu-Assi, R; Khurana, S; Moore, D
Abstract : Background: The role of high‐resolution esophageal impedance manometry (HRIM) for establishing risk for dysphagia after anti‐reflux surgery is unclear. We conducted a prospective study of children with primary gastroesophageal reflux (GER) disease, for whom symptoms of dysphagia were determined pre‐operatively and then post‐operatively and we examined for features that may predict post‐operative dysphagia. Methods: Thirteen children (aged 6.8–15.5 years) undergoing work‐up prior to 360 o Nissen fundoplication were included in the study. A dysphagia score assessed symptoms at pre‐operative study and post‐operatively (mean 1.4 years). A HRIM procedure recorded 5‐ml liquid, 5‐ml viscous and 2‐cm solid boluses. We assessed esophageal motility, esophago‐gastric junction (EGJ) morphology, EGJ contractility and pressure‐flow variables indicative of bolus distension pressures and bolus clearance pressures. A composite pressure‐flow index score was also derived. Results: Pre‐operative pressure‐flow index was positively correlated with post‐operative dysphagia score (viscous bolus r = 0.771, p < 0.005). Of three variables that comprise the pressure‐flow index, the ramp pressure measured during bolus clearance was the main driver of the effect seen (viscous bolus r = 0.819, p < 0.005). Conclusions: In order to mitigate symptoms in relation to anti‐reflux surgery, dysphagia symptoms and esophageal function need to be pre‐operatively assessed. In patients with normal motility, an elevated pressure‐flow index may predict post‐operative dysphagia.